Anatomic Structures at Risk When Utilizing Percutaneous Intramedullary Fibular Screw Fixation for Lateral Malleolus Fractures: A Cadaveric Study. Issue 4 (November 2022) - Shah, Ashish; Littlefield, Zachary; Boyd, Brandon; Patch, David A.; Jacob, Roshan; Prahad, Srihari R.; Reed, Logan; Elphingstone, Joseph; Young, Sean M.; Sanchez, Thomas; Sankey, Turner
Category: Ankle Introduction/Purpose: Isolated lateral malleolus fractures are a common ankle fracture that a foot and ankle surgeon will encounter. Retrograde intramedullary fixation for unstable lateral malleolus fractures has become a viable option for patients at higher risk for potentially devastating wound complications. The aim of this cadaveric study was to assess the relative risk of injuring adjacent anatomic structures with percutaneous implantation of an intramedullary fibular screw for lateral malleolus fractures to minimize iatrogenic injury. Methods: Seven fresh-frozen below-the-knee cadaver specimens were used for this study. Prior to investigations, specimens were inspected with fluoroscopic radiographs for preexisting pathology or prior surgical intervention. Lateral dissection of the lateral malleolus was performed after screw placement to determine the proximity of the peroneus longus (PL), peroneus brevis (PB), and sural nerve (SN) to the inserted hardware. The mean, standard deviation, and range for distances were calculated for all structures. Analysis of variance (ANOVA) was used to determine statistical significance. Results: Percutaneous intramedullary fibular screw placement was performed in seven specimens, six females and one male, with an average age of 79.3 +- 8.1 years. Amongst the seven specimens, only one resulted in an injury to a structure of interest (sural nerve). The peroneus longus and peroneus brevis were not injured in any of the specimens. Table 1 shows the average distance between the guidewire and each structure of interest. Conclusion: This study shows the potential risks to lateral structures when placing an intramedullary fibular screw for unstable lateral malleolus fractures. We suggest that orthopedic surgeons exercise caution when performing critical steps of the procedure to minimize avoidable injury to structures of importance that may increase the morbidity of the patient.